Satsang, A Contemporary Religion of Convergence (European Journal of Behavioral Sciences, 2019)
The purpose of this study is to identify the similarities in beliefs, traditions, and rituals of all the existing religions or religious practices of the world and explore the possibilities of religious convergence. The study found that although there are many similarities in the principles of the major religions in the world none of the old and existing religions offer religious convergence where a union of existing religions is possible. Satsang, a contemporary religion founded by Sree Sree Thakur Anukulchandra (1888-1969), a prominent philanthropist and one of the greatest philosophers of recent times, supports convergence. This paper explained the importance of initiation in the creed of a superior ideal in each of the major religions. It has also examined in detail how people from any faith, race or religion can practice the principles of Satsang doctrine along with existing religious practices to accomplish the spiritual quests of individuals.